Shady Facebook 'whistleblower' wants more censorship and crackdown on US adversaries - Moderate Rebels (2021)
Max Blumenthal and Ben Norton discuss shady Facebook "whistleblower" Frances Haugen and how her testimony only helps US spy agencies, justifying further government censorship while demonizing Washington's Official Enemies, from China to Iran, Myanmar to Ethiopia. ||| Moderate Rebels ||| Please consider supporting us on PATREON: https://www.patreon.com/ModerateRebels Website: https://moderaterebels.com Twitter: https://twitter.com/moderate_rebels Facebook: https://facebook.com/moderaterebelsradio Soundcloud: https://soundcloud.com/moderaterebels Minds: https://minds.com/moderaterebels #ModerateRebels